1978
DOI: 10.1128/jvi.26.2.325-334.1978
|View full text |Cite
|
Sign up to set email alerts
|

Recently replicated simian virus 40 DNA is a preferential template for transcription and replication

Abstract: The template activities for the processes of replication and transcription were compared for recently replicated ("new") and uniformly labeled ("old") simian virus 40 (SV40) DNA in infected monkey cells (line TC7). New SV40DNA (pulselabeled for 1 h) served as a template for a second round of replication withl a relatively high probability (8% of the DNA replicated per h) for a period of 5 h, after which time its template activity rapidly decreased by severalfold. Old SV40 DNA (labeled for 24 h) functioned as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

1979
1979
1986
1986

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 33 publications
(2 reference statements)
2
12
0
Order By: Relevance
“…tate replication complexes without affecting transcription complexes. Several authors have reached analogous conclusions in the simian virus 40 system (3,12,14). They have found that the viral DNA template for late transcription is not a replicating DNA molecule.…”
Section: Resultsmentioning
confidence: 76%
“…tate replication complexes without affecting transcription complexes. Several authors have reached analogous conclusions in the simian virus 40 system (3,12,14). They have found that the viral DNA template for late transcription is not a replicating DNA molecule.…”
Section: Resultsmentioning
confidence: 76%
“…A role for maturation proteins was postulated by Roman and Dulbecco (22) and Roman (21). Similarly, Garber et al (8) and Baumgartner et al (1) compared their determinations on the rate of encapsidation of DNA with the published data on the kinetics of reentry of DNA into replication (9,21,22), and postulated an association between the two pathways.…”
mentioning
confidence: 97%
“…More than 90% of the [3H]DNA from both irradiated and unirradiated cells was covalently closed; thus, degradation of the pulse label cannot be the cause of the inhibition. Since a fraction of the prelabeled DNA is used as a template for further DNA synthesis (12,24) and pyrimidine dimers appear to block replication forks (4, 5), we asked whether the [3H]DNA was accumulating as parental strands of replicative intermediates whose completion was inhibited. By T = 2 h, the fraction of label from the NPC-I pool which behaved as replicative intermediates on benzoylated-napthoylated DEAE (BND)-cellulose columns (15) was 5 to 6% in unirradiated cultures and 13 to 19% in the cultures irradiated with 108 J m-2; irradiation of purified form I DNA with this fluence increased the fraction retarded on BND-cellulose from…”
Section: Resultsmentioning
confidence: 99%